Plating Nikel pada Kawat Tembaga untuk Meningkatkan Kepekaan sebagai Sensor Suhu Rendah - Siti Zahra Helmalia Putri Zahra; Moh. Toifur (Universitas Nurul Huda, 2025)
This research aims to determine the sensitivity of the sensor as a low temperature sensor from the Ni-coated Cu coil with electroplating technique. The deposition parameters are set, namely the electrolyte solution by dissolving NiSO4, NiCl2, H3BO4 and distilled water, voltage 4.5V, electrode distance 4 cm, electrolyte temperature 60 ° C for 4 minutes. The sensor sensitivity test was carried out by varying the temperature from 0˚C to -150˚C by inserting the sensor in a liquid nitrogen thermos and lifting it to its original position. Acquisition of temperature and voltage data at any time was carried out with the help of a transducer. Based on the results of the study, the Voltage-Temperature curve shows that the sensitivity value obtained by the Cu coil is S(T) = -1E-06 T - 5E-05 and the Cu/Ni coil S(T) = -4E-06 T - 0.0002. The results of the T=-200 ˚C projection show that the sensitivity value of the Cu/Ni coil has a greater value than the Cu coil. The Cu coil shows a value of 0.00035 while the Cu/Ni coil is 0.0014. So Ni has an effect on increasing the sensitivity of the Cu coil as a low temperature sensor.